The levelling effect of product market competition on gender wage discrimination - Boris Hirsch; Michael Oberfichtner; Claus Schnabel (IZA Journal of Labor Economics, 2014)
Using linked employer-employee panel data for West Germany that include direct information on the competition faced by plants, we investigate the effect of product market competition on the gender pay gap. Controlling for match fixed effects, we find that intensified competition significantly lowers the unexplained gap in plants with neither collective agreements nor a works council. Conversely, there is no effect in plants with these types of worker codetermination, which are unlikely to have enough discretion to adjust wages in the short run. We also document a larger competition effect in plants with few females in their workforces. Our findings are in line with Beckerian taste-based employer wage discrimination that is limited by competitive forces.
Keywords: J16; J31; J71; 330; Gender pay gap; Discrimination; Product market competition